2001
DOI: 10.1161/01.cir.103.19.2328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abciximab on the Architecture of Platelet-Rich Clots in Patients With Acute Myocardial Infarction Undergoing Primary Coronary Intervention

Abstract: Abciximab dramatically reduces platelet aggregate size and increases the fibrin accessibility of ex vivo PRC in AMI patients. These modifications could participate in the better coronary artery patency observed with abciximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 13 publications
1
31
0
2
Order By: Relevance
“…[63][64][65][66] This is attributed to the tightly contracted fibrin network; however, it may also result from crosslinking of additional a 2 AP to fibrin as a result of the high local concentration of FXIII-A. It has recently been shown that supplementing blood of thrombocytopenic patients with FXIII, thrombin activatable fibrinolysis inhibitor, or fibrinogen increases clot strength and decreases lysis.…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65][66] This is attributed to the tightly contracted fibrin network; however, it may also result from crosslinking of additional a 2 AP to fibrin as a result of the high local concentration of FXIII-A. It has recently been shown that supplementing blood of thrombocytopenic patients with FXIII, thrombin activatable fibrinolysis inhibitor, or fibrinogen increases clot strength and decreases lysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, GP IIb/IIIa receptor antagonists were used more frequently in TIMI 0-1 and 2 groups. It is known that intravenous administration of these antagonists not only blocks the final common pathway for platelet aggregation and prevents aggregation regardless of the initial activating stimulus, but could also enable lysis of an acutely formed platelet thrombus [19,20]. Although proximal and distal mechanical protection devices and thrombectomy catheters may also prevent from distal embolization, their effects on myocardial perfusion and clinical outcome in patients with AMI remain unclear and controversial [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, none was found to promptly and effectively restore the coronary flow. 10) Recently, administration of a platelet glycoprotein IIb/IIIa antagonist, abciximab, was reported to be able to enhance the fibrinolytic effect, change the thrombus architecture, and increase the coronary flow in vitro 11) and platelet activation was considered an underlying mechanism in patients with an acute myocardial infarction. Using quantitative myocardial contrast echocardiographic study, tirofiban also improved microvascular flow and reduced the infarct area after coronary occlusion/reperfusion in open-chest dogs.…”
Section: Discussionmentioning
confidence: 99%